Consistency of spatiotemporal sound features supports the use of passive acoustics for long‐term monitoring. (12th July 2017) - Parmentier, E.; Di Iorio, L.; Picciulin, M.; Malavasi, S.; Lagardère, J.‐P.; Bertucci, F.
Abstract : Many studies stress the usefulness of fish calls as effective indicators of distinct species occurrence. However, most of these studies have been undertaken in a particular area and during restricted periods of time. This study used passive acoustic methods to follow the brown meagre Sciaena umbra at relevant temporal and spatial scales. The comparisons highlight the capability to identify S. umbra during a period of 17 years in different Mediterranean regions, clearly supporting the usefulness of acoustic monitoring to discover and protect aggregation sites of this endangered species. Abstract: Many studies stress the usefulness of fish calls as effective indicators of distinct species occurrence. However, most of these studies have been undertaken in a given area and during restricted periods of time. There is a need to show passive acoustic monitoring is a reliable method to study vocal species over space and time. This study aims to use passive acoustic methods to follow the brown meagre Sciaena umbra at relevant temporal and spatial scales. Specimens of S. umbra were recorded in both aquarium and in the field. In situ recordings were made at two regions (Corsica and Sardinia) during four summers (2008–2012–2013–2015). Temporal and frequency parameters of the fish calls were collected by different teams and compared to test the ability to unequivocally identify the fish sound. The comparison between our data and the bibliography highlights the capability to identify S. umbra during a period of 17 years in different Mediterranean regions, clearly supporting the usefulness of acoustic monitoring to discover and protect aggregation sites of this endangered species. The sound producing mechanism in S. umbra consists of high‐speed sonic muscles surrounding dorsally the posterior end of the swim bladder, which can explain the low acoustic variability that helps in the species identification. Similar mechanisms are found in other Sciaenidae, suggesting that a similar conclusion can be drawn for many other adult sciaenids that could be used as sentinel species. This study should be of high interest to policymakers and scientists because it shows passive acoustic can be confidently used in resource management.